A knowledge, attitudes, and practices survey concerning blood donation among Libyans - A J Goldsmith; N M Gebril; D Sondag Thull; Y E Abdella; L Barski; P Y Malgor; F Bossolini; O Aldaher; Cees Theodoor Smit Sibinga (Global Journal of Transfusion Medicine, 2023)
Background and Objectives: Libya's blood transfusion system suffers from chronic blood shortages due to low rates of voluntary, nonremunerated blood donors (VNRBDs). Over 90% of blood donations are for family members or friends of donors, and only 1% of donors are women. This study aimed to understand the barriers and motivations for blood donation in Libya to support sensitization campaigns. Methods: A knowledge, attitudes, and practices survey was conducted with 896 people in seven Libyan cities where blood banks are located. Key informant interviews were conducted with blood donors, staff, and experts across all seven cities. Thematic content analysis was conducted for the qualitative data, and SPSS was used to produce descriptive statistics. Results: There was a strong awareness of blood donation and the uses of donated blood within the surveyed population. Most respondents who had not donated blood had considered donating. The association between blood donation and Hijama, the traditional medical bloodletting practice, was cited as a sensitization experience for some VNRBDs. The common barriers for potential female donors included misconceptions about female eligibility, social norms, and constraints based on the opinions of their husbands. Conclusion: Sensitization campaigns can encourage people to donate for the first time to dispel fears and reinforce the connection between blood donation and altruistic/religious giving. Religious institutions, including mosques and Hijama centers, must be engaged to emphasize that blood donation is ethically compatible with Islam. Campaigns should also highlight that women are eligible to donate blood.